Preprints: the multidisciplinary preprint platform (MDPI AG, 2016)
Preprints is a multidisciplinary platform dedicated to making early versions of research outputs available, including original research articles and reviews. Content on Preprints is not yet peer-reviewed and can receive feedback from readers. Updated versions of manuscripts can be uploaded by authors at any time.